Hysterectomy with opportunistic salpingectomy and its influence on structural-functional parameters of ovarian tissue - Proshchenko, Olha; Ventskivska, Iryna (ScienceRise: Medical Science, 2022)
The study examined the development of posthysterectomy syndrome in patients after hysterectomy with preservation of ovarian tissue. The aim of the study was to assess the functionality of ovarian tissue in patients with hysterectomy and opportunistic salpingectomy performed for uterine fibroids. Materials and methods of the research. The study was performed in 160 women of reproductive age. The first group included 90 patients after vaginal hysterectomy with tubectomy and associated with laparoscopy, the second group - 70 patients after abdominal hysterectomy with tubectomy. The control group included 50 women of reproductive age 45.7±1.3 years with asymptomatic fibroids. The diagnostic algorithm included assessment of hormonal status and instrumental study of structural and functional parameters of ovarian tissue both at the stage of preoperative observation and for 12 months, 3 and 5 years after surgery. Research results and their discussion. At the preoperative stage in both groups found a higher percentage of thyroid disease, hypertension and metabolic disorders, as well as combined proliferative processes of the uterus. Normal ultrasound picture of the ovaries was found in 67.8 % - in the first group and in 47.1 % - in the second group. Significant increase in blood flow in the ovarian artery, in the remote period showing atrophic changes with the development of ovarian depletion syndrome. Assessment of hormonal status in both groups shows marked changes in baseline levels of gonadotropic hormones (FSH and LH): increase in baseline FSH levels by 2.2 times, LH - 1.5 times against the control group (p <0.05), dyshormonal disorders persist for up to 5 years after surgery in one third of cases, and up to 36 months - there is an increase in the proportion of cystic and trophic changes, most pronounced in patients with reduced ovarian reserve, dysmetabolic manifestations and combined proliferative processes of the uterus and appendages before surgery, and syndrome chronic pelvic pain and venous pelvic blood supply in the postoperative period. Conclusions. The technique of performing a hysterectomy does not have a significant effect on the functional state of the ovaries in the long term. The main indicators of ovarian blood flow and steroid hormone production after hysterectomy with opportunistic salpingectomy for uterine fibroids are close to the reference values up to 36 months postoperatively